Development of a Suspension Microarray for the Genotyping of African Swine Fever Virus Targeting the SNPs in the C‐Terminal End of the p72 Gene Region of the Genome. Issue 4 (8th July 2012) - LeBlanc, N.; Cortey, M.; Fernandez Pinero, J.; Gallardo, C.; Masembe, C.; Okurut, A. R.; Heath, L.; van Heerden, J.; Sánchez‐Vizcaino, J. M.; Ståhl, K.; Belák, S.
Summary African swine fever virus (ASFV) causes one of the most dreaded transboundary animal diseases (TADs) in Suidae. African swine fever (ASF) often causes high rates of morbidity and mortality, which can reach 100% in domestic swine. To date, serological diagnosis has the drawback of not being able to differentiate variants of this virus. Previous studies have identified the 22 genotypes based on sequence variation in the C‐terminal region of the p72 gene, which has become the standard for categorizing ASFVs. This article describes a genotyping assay developed using a segment of PCR‐amplified genomic DNA of approximately 450 bp, which encompasses the C‐terminal end of the p72 gene. Complementary paired DNA probes of 15 or 17 bp in length, which are identical except for a single nucleotide polymorphism (SNP) in the central position, were designed to either individually or in combination differentiate between the 22 genotypes. The assay was developed using xMAP technology; probes were covalently linked to microspheres, hybridized to PCR product, labelled with a reporter and read in the Luminex 200 analyzer. Characterization of the sample was performed by comparing fluorescence of the paired SNP probes, that is, the probe with higher fluorescence in a complementary pair identified the SNP that a particular sample possessed. In the final assay, a total of 52 probes were employed, 24 SNP pairs and 4 for general detection. One or more samples from each of the 22 genotypes were tested. The assay was able to detect and distinguish all 22 genotypes. This novel assay provides a powerful novel tool for the simultaneous rapid diagnosis and genotypic differentiation of ASF.